Performance Efficiency of the Village Team in Na Bo Kham Subdistrict Mueang Kamphaeng Phet District Kamphaeng Phet Province - Kingpuang, Polchai; Bodeerat, Chot; Dokchan, Phasakorn (Journal of Graduate MCU KhonKaen Campus, 2025)
This independent research aimed to 1) study the level of performance efficiency of the Village Security Team, 2) compare personal factors with the performance efficiency of the Village Security Team, 3) study recommendations for the development of the performance efficiency of the Village Security Team. The research was conducted according to the quantitative research methodology using a survey research study. The sample group was 382 people from 8 villages. The instrument was a questionnaire. Data were analyzed using statistics, frequency, percentage, mean, standard deviation, and t-test, F-test. The research results found that. 1) The overall level of effectiveness of the village security team was at a high level. 2) The comparison of personal factors and the performance efficiency of the village security team found that people with different genders, ages, education, occupations, and average monthly incomes had no different opinions on the performance efficiency of the village security team. Therefore, the hypothesis was rejected. 3) The suggestions for developing the performance of the village security team found that the compensation, allowances and various benefits should be considered, announcing honors or praising the workers should be organized, and the performance according to the roles and duties of the village security team (VSC) should be developed consistently and continuously to keep up with the changing situation.